New Sunday Times, 26 April 2009 (The New Straits Times Press (M) Bhd, 2009)
When Open University Malaysia (OUM) cae to the fore in 2001, it breathed fresh air into the local higher education milieu. As a novice open and distance learning (ODL) institution, the university strived to reach out to people from different walks of life to democratise education.